(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This thesis analyzes the significance and future prospects of teaching higher mathematics in medical universities. Due to the digitalization of the healthcare system, the emergence of biomedical engineering solutions, and the advancement of evidence-based medicine, mathematical literacy, analytical thinking, and biostatistical skills have become essential competencies for medical students. The thesis addresses key challenges in teaching higher mathematics, the necessity of integrating practical modules (biostatistics, mathematical modeling, epidemiological analysis) into the curriculum, and the modernization of teaching through digital technologies. Furthermore, it emphasizes that interdisciplinary collaboration and updated curricula serve to enhance the scientific and analytical potential of medical professionals.